DESIGN AND DEVELOPMENT OF VIDEO TUTORIAL FOR CREATING SOCIAL MEDIA MARKETING CONTENT IN THE FOOD AND BEVERAGE BUSINESS USING THE MDLC METHOD - Yefta Christian; Arbiwijaya Kwek (Universitas Internasional Batam, 2022)
Internet and social media have already been part of our lives. Nowadays, social media is not only used for communication and sharing but can also be used for business. By creating content in social media, we can use social media as one of our digital marketing strategies. This study aimed at designing and developing a video tutorial for creating social media marketing content in the food and beverage business. This study uses the MDLC (Multimedia Development Life Cycle) as the method. The result of this study is a video tutorial that is uploaded to YouTube. By designing and developing a video, we hope it can help others for creating social media marketing content.